Gijon has fallen! - Labour and Socialist International ; Schevenels, Walter, b. 1894 ; Brouckère, Louis de, 1870-1951; Adler, Friedrich, 1879-1960; Citrine, Walter, 1887-1983
1937 016b-0043-001 292/946/16b/47(i)